Topiramate-Induced Cough in Migraine Prophylaxis - J Gordon Millichap (Pediatric Neurology Briefs, 2009)
Three adults who developed intractable cough during topiramate prophylaxis of migraine are reported from the University of Padua and other centers in Italy.